Our First Diet After Birth is Breast Milk, But the Vital Lipids in Whole Milk are Now Destroyed by Homogenization - M.D, Thomas Tallberg (The International Journal of Biotechnology, 2014)
Lipidomics is the function of billions of vital lipid molecules forming our brain and spinal cord. In the serum of cancer patients there could transiently appear lipids stemming from the central nervous system (CNS), following herpes virus infections. Dietary substitution utilizing CNS-lipid precursors as in whole milk could compensate this lipid depletion.Oral supplementation led to physiologic therapeutic effects. Lipidomics, depicts studies on neurobiology describing the clinical function of billions of vital lipids contained in our brain and spinal cord, articulated as a harmonious synaptogenesis. The aim is to relate certain clinical features and expressions of this immensely complex panel of psychodynamic functions regulated by this multifaceted brain-lipid network. Our daily mental function and stress caused by excessive exercise consumes certain of these vital CNS-lipid molecules. Healthy reconstruction of this physiologic consumption of CNS-lipids proceeds during our sleep providing that our serum contains vital CNS-lipid precursor components supplied via our diet containing whole milk in which the cream (lipoprotein) is not destroyed by homogenisation. A combined dietary ingestion of whole milk together with prion-free CNS-lipids can restore normal cell induction, improve the motor, and mental balance of patients.